Indonesian Language Acquisition of Arabian Young Learner - Asep Anwar Siddiq (Kopertais Wilayah I DKI Jakarta dan Banten, 2020)
By using language, people can convey their message and express their ideas verbally or in writing so that they can work together and get along with each other. People realize that without language they cannot interact with each other. There are so many languages in the world. It depends on each country, even though they can build social interaction through international languages. There are a number of different countries in the world, such as Britain, France, Spain, China, Japan and Arabia. There are many Arabian who come to Indonesia with various purposes, such as trading, preaching and others. But the disadvantage is that they are not able to speak Indonesian. So it is difficult for them to communicate with Indonesian people. Arabians find it is very difficult to speak Indonesian mainly because their pronunciation is very different from Indonesian people.